Exploring the need for fertility education: A cross-sectional study of healthcare professionals and students’ knowledge of fertility and fertility preservation - Ana GALHARDO; Catarina SALVADO; Soraia MONIZ; Marina Cunha; Ilda MASSANO-CARDOSO (Journal of Health and Social Sciences)
Introduction: Increasing attention has been directed toward fertility and fertility preservation (both for medical and non-medical reasons) worldwide. Nevertheless, previous studies have reported a lack of fertility awareness in the general population, healthcare providers, and medical students. This study aimed to explore health professionals’ and students’ fertility knowledge, fertility preservation knowledge and attitudes, and interest in accessing more information. Methods: The sample consisted of 309 participants (214 students; 95 professionals) from medicine, nursing, and psychology. Participants completed an online questionnaire addressing knowledge about fertility and fertility preservation, attitudes towards fertility preservation, and interest in receiving more information. Results: Most participants were aware of the infertility definition and prevalence, but 41.2% of students and 37.9% of professionals needed to recognize that men's age may also impact fertility. Concerning in vitro fertilization (IVF) success rates, 38.3% of students and 35.8% of professionals underestimated the IVF success rates, whereas 33.2% and 27.8%, respectively, overestimated these rates. Participants' answers regarding factors affecting fertility showed that more than half of the participants, more than half of the students (54.6%), and the professionals (60%) overestimated the age of women’s fertility decline. Oocyte cryopreservation was the fertility preservation option they knew best. Health professionals and students mostly agreed that providing fertility preservation information should be part of regular healthcare and mentioned that receiving information about fertility preservation would be helpful. Professionals revealed higher knowledge when compared to students. Conclusions: Overall, despite having some information, professionals and students still lack sufficient knowledge to support their patients. These results highlight the relevance of designing training and information opportunities to enhance knowledge on the topics of fertility awareness and fertility preservation.